The Geology Of South Florida With Emphasis On Deep Foundations - Edwin W. Hickey (Deep Foundations Institute, 2003)
This paper briefly discusses the geologic conditions in South Florida relative to the design, construction, and performance of deep foundations. The subsurface conditions in this area are unique in that the rock layers are highly porous and often very soft, and are sandwiched between layers of typically loose, uncemented quartz fine sands. Due to the high porosity of the Miami Limestone, 4-inch diameter rock coring is often required to obtain intact samples, and dewatering of excavations is sometimes difficult or impossible. The sand layers, typically tens of feet thick, are very loose to loose in relative density and have been the cause of unexpected large, deep foundation settlements. The engineering properties of the various geologic formations are discussed, along with typical deep foundation types used in the Miami area prior to and after 1980.